O papel da contabilidade no provimento de informações para a avaliação do desempenho empresarial - Valdirene Gasparetto (Revista Contemporânea de Contabilidade, 2004)
The role of accounting in the provision of information for the managing performance evaluation Accounting is an important supplier of information for the managing performance evaluation. In order to improve the way the performance of enterprises is evaluated several models have been envisaged recently and despite the criticism of the accounting indices that are traditionally used by enterprises to evaluate their performance, they are acknowledged as still important. Instead of replacing them, as some authors have proposed, they ought to be complemented with indices of other areas and it is the duty of accounting to undertake the right actions in order to identify the current changes in the business environment so as to register the accounting events adequately, provide measures to invest the accounting data base with flexibility and provide useful information for the new objectives